Development of Problem-Based Learning Integrated STEM E-Student Worksheet to Foster Students' Scientific Literacy Competence - Maslichah, Dina; Astuti, Budi; Rusilowati, Ani; Hartono, Hartono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study aims to develop a STEM-integrated Problem-Based Learning (PBL) E-Student Worksheet that is suitable for use in teaching and effective in fostering students' scientific literacy competence, as well as to analyze students' responses to the use of the E-Worksheet. The research adopts a Research and Development (R&D) approach using the ADDIE development model. The stages conducted in the study include: 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data collection techniques employed include interviews, questionnaires, tests, and documentation. Data were analyzed using test instrument validation analysis, feasibility analysis, and effectiveness analysis of the E-Student Worksheet. The results of the study indicate that the STEM-integrated PBL-based E-Worksheet on the topic of sound waves is suitable for use in learning, with a material feasibility test score of 89.77%, a media feasibility test score of 90.17%, and a readability test score of 86.89%. The STEM-integrated PBL-based E-Worksheets was also found to be effective in fostering students' scientific literacy competence. On the indicator of explaining scientific phenomena, a score of 83.64% was achieved; on the indicator of evaluating and designing scientific investigations, a score of 75.76% was achieved; and on the indicator of interpreting data and scientific evidence, a score of 80.00% was achieved. Furthermore, the STEM-integrated PBL-based E-Student Worksheet received positive feedback from students, with a response rate of 79.59%.